(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Creative thinking is crucial in students' acquisition and development of clothing skills. This research paper investigates the impact of creative thinking on students’ abilities to design, create, and innovate within the context of clothing and fashion. The study participants included one hundred thirteen (n = 113) students at Federal College of Education, Technical, Omoku, River State, Nigeria. Self-report measures were used to obtain data. The linear regression analysis performed to examine the effect of creative thinking on clothing skills among the respondents revealed that creative thinking significantly predicted clothing skills, F (1, 111) = 6.231, p > 0.00. In particular, the result showed that creative thinking accounted for about 42.2% of the variation in clothing skills among the respondents. The study contributes to the understanding of creative learning in the context of clothing education. By recognizing the pivotal role of creative thinking, educators can better prepare students for careers in fashion and textiles. We conclude by emphasizing the importance of integrating creativity into clothing curricula.